Aftershocks from the Global Food Crisis - Mendoza, Ronald U (Archīum Ateneo, 2010)
When the global economic crisis began to unfold in full force in 2009, high food and fuel prices received much less attention. Nevertheless, an analysis of international and national data suggests that a food crisis persists in many countries a full two years since food price shocks began to unfold in early 2008. This spells more difficult days ahead for many poor households whose purchasing power continues to be squeezed, first by high food prices and later by a decline in income as a result of the global economic crisis. This has particularly intense impacts on children as the foundation of health and well-being is laid in childhood. Evidence shows that where children and mothers have poor health, nutrition and education the consequences can last a lifetime. Children and poor households will continue to face severe stress, as many of the factors that contributed to high and volatile food prices remain unaddressed.